CALM Interventions: Behavioral Health Crisis Assessment, Linkage, and Management Improve Patient Care. (January 2018) - Lester, Natalie A.; Thompson, Laura R.; Herget, Kendal; Stephens, Julie A.; Campo, John V.; Adkins, Eric J.; Terndrup, Thomas E.; Moffatt-Bruce, Susan
Emergency departments (EDs) have seen rising numbers of patients in psychiatric crises, patient boarding, and throughput delays. This study describes and evaluates the impact of a Crisis Assessment Linkage and Management (CALM) service designed to manage behavioral health crises. A year-to-year comparison was performed before (n = 2211 ED visits) and after implementation of CALM (n = 2387). CALM was associated with reductions in median ED and hospital length of stay (LOS) from 9.5 to 7.3 hours and 46.2 to 31.4 hours, respectively. Mean transformed ED LOS decreased by 32.4% ( P < .001). The CALM model improved patient care and throughput metrics by proactively managing behavioral health crises.